Leaders of Public Service Organizations: Improve Library Excellent Service - Daniel P Hutapea (Universitas Wijaya Kusuma Surabaya, 2019)
This study aims to determine the role of leaders in improving library excellent service. The object of research focuses on content the role of the leader in library excellent services. The scope of the study examines the embodiment of the leader's role performance in library excellent services. Research is a historical approach, has the main characteristics of critical research about developments in reality. Utilization of primary data is the main source of information and data search methods using library research. Using qualitative descriptive analysis and content analysis to analyze the importance of understanding the role of leaders, the performance of librarians and excellent service and its application in library organizations. The observation was carried out as supporting theoretical construction. The results showed that the role of leaders in improving library excellent service is; (1). Planning strategies and effective communication in the working mechanism of library organizations. (2). Improving the performance of librarians through enhancing professionalism and competence using an assessment of librarian performance measures